Three-dimensional composite solid electrolyte membrane, preparation method thereof and all-solid-state lithium metal battery
By designing a three-dimensional composite solid electrolyte membrane, the coordinated cooperation of the homogeneous gel buffer layer, porous intermediate layer and polymer base layer is solved, and the problems of low ionic conductivity and insufficient mechanical performance at room temperature are achieved, and the battery performance is improved.
Patent Information
- Application Number
- CN202411911195.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-02-28
AI Technical Summary
The problems of low ionic conductivity and insufficient mechanical properties of existing solid electrolytes at room temperature lead to limited battery performance, especially chemical side reactions and interface impedance.
A three-dimensional composite solid electrolyte membrane is designed, including a homogeneous gel buffer layer, a porous intermediate layer and a polymer base layer. Through the coordinated cooperation of these layers, the mechanical strength and ionic conductivity of the electrolyte membrane are improved and chemical side reactions are inhibited.
It improves the safety performance, cycle performance and rate performance of the battery, extends the cycle life of the battery, and reduces the interface impedance.
Smart Images

Figure CN119542525A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a three-dimensional composite solid electrolyte membrane and a preparation method thereof, and an all-solid-state lithium metal battery. Background Art
[0002] In conventional lithium-ion batteries, the organic solvents contained in the liquid electrolyte are flammable. Once the temperature inside the battery rises or a short circuit occurs, these organic solvents are extremely easy to burn, causing a fire, posing a serious threat to the life safety of personnel and the normal operation of equipment.
[0003] Common solid electrolytes are divided into polymer electrolytes and oxide electrolytes. Among them, polymer electrolytes have good flexibility, are easy to form films, have simple preparation processes, and have good interfacial wettability with electrodes, but their room temperature ionic conductivity is low, which seriously affects the performance of the battery; oxide electrolytes have higher ionic conductivity and a wider electrochemical window, but they are more brittle and have poor interfacial contact with the electrodes, which seriously limits their practical application. In addition, serious chemical side reactions will occur between solid electrolytes and positive and negative electrodes, resulting in the formation of a thick interfacial layer that is difficult to control, and the interfacial impedance increases sharply, affecting the overall electrochemical performance of the battery.
[0004] Therefore, how to further improve the ionic conductivity and mechanical properties of solid electrolytes, while inhibiting the chemical side reactions between the solid electrolytes and the positive and negative electrodes, and reducing the interface impedance, thereby improving the safety performance, cycle performance and rate performance of the battery, is a technical problem that needs to be solved urgently. Summary of the invention
[0005] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a three-dimensional composite solid electrolyte membrane and a preparation method thereof and an all-solid-state lithium metal battery. In the three-dimensional composite solid electrolyte membrane designed by the present invention, the homogeneous gel buffer layer has high mechanical strength and elastic modulus, which can prevent lithium dendrites from piercing the diaphragm and causing battery short circuit; the porous intermediate layer can increase the contact area between the membrane layers on both sides and the electrodes, provide more transmission channels for lithium ions, reduce transmission resistance, improve ion conductivity, enable the battery to charge and discharge faster, and improve the battery's rate performance. At the same time, it also has excellent mechanical stability, which prolongs the battery's cycle life; the polymer base layer has excellent mechanical strength and interface stability. The three membrane layers work together to effectively inhibit the chemical side reactions between the three-dimensional composite solid electrolyte membrane and the positive and negative electrodes, reduce interface impedance, and improve the overall electrochemical performance of the battery.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a three-dimensional composite solid electrolyte membrane, comprising a stacked homogeneous gel buffer layer, a porous intermediate layer and a polymer substrate layer.
[0008] In the three-dimensional composite solid electrolyte membrane designed by the present invention, the homogeneous gel buffer layer has high mechanical strength and elastic modulus, wherein the lithium ion transmission is smooth, the ion conductivity is high, and it is in direct contact with the lithium metal negative electrode. When lithium dendrites are generated, the buffer structure of the homogeneous gel buffer layer can apply a certain resistance to limit the growth and extension of lithium dendrites, and prevent them from piercing the diaphragm to cause a battery short circuit; the porous intermediate layer can increase the contact area between the membrane layer on both sides and the electrode, provide more transmission channels for lithium ions, reduce the resistance of ion transmission, thereby improving the ion conductivity, enabling the battery to charge and discharge more quickly, and improving the rate performance of the battery. At the same time, the porous intermediate layer also has excellent mechanical stability, which enables the three-dimensional composite solid electrolyte membrane to better withstand the stress generated by the volume change of the electrode material during the battery charging and discharging process, reduce the risk of membrane rupture and damage, and improve the cycle life of the battery; the polymer substrate layer has excellent mechanical strength and interface stability. Therefore, the three membrane layers cooperate with each other to effectively inhibit the chemical side reactions between the three-dimensional composite solid electrolyte membrane and the positive and negative electrodes, reduce the interface impedance, and improve the overall electrochemical performance of the battery.
[0009] Preferably, the thickness of the homogeneous gel buffer layer is 5-20 μm, for example, 5 μm, 10 μm, 15 μm or 20 μm, etc., preferably 5-15 μm.
[0010] In the present invention, the homogeneous gel buffer layer with suitable thickness has high mechanical strength and elastic modulus, high ionic conductivity, and is helpful to limit the growth and extension of dendrites, thereby preventing them from piercing the diaphragm and causing battery short circuit.
[0011] Preferably, the thickness of the porous intermediate layer is 10-30 μm, for example, 10 μm, 15 μm, 20 μm, 25 μm or 30 μm, etc., preferably 10-20 μm.
[0012] In the present invention, the porous intermediate layer of appropriate thickness can provide more transmission channels for lithium ions, reduce the resistance of ion transmission, and improve ion conductivity. At the same time, it also has excellent mechanical stability, can better withstand the stress caused by the volume change of the electrode material, and reduce the risk of membrane rupture and damage.
[0013] Preferably, the thickness of the polymer substrate layer is 10-20 μm, for example, 10 μm, 15 μm or 20 μm, etc., preferably 10-15 μm.
[0014] In the present invention, the polymer base layer of appropriate thickness has excellent mechanical strength and interface stability, which helps to improve the overall structural stability of the entire composite solid electrolyte membrane, so that it can better withstand external pressure, tension and other mechanical effects during use, and avoid rupture, stratification and the like.
[0015] Preferably, the thickness ratio of the homogeneous gel buffer layer, the porous intermediate layer and the polymer base layer is (0.5-1):(0.6-1.5):1, wherein the selection range of the homogeneous gel buffer layer "0.5-1" can be, for example, 0.5, 0.6, 0.7, 0.8, 0.9 or 1, and the selection range of the porous intermediate layer "0.6-1.5" can be, for example, 0.6, 0.8, 1, 1.2 or 1.5, etc.
[0016] In the present invention, a homogeneous gel buffer layer, a porous intermediate layer and a polymer base layer with a suitable thickness ratio cooperate with each other, and utilize a synergistic effect to greatly improve the ionic conductivity and mechanical properties of the three-dimensional composite solid electrolyte membrane, while greatly inhibiting the chemical side reactions between the three-dimensional composite solid electrolyte membrane and the positive and negative electrodes, reducing the interface impedance, thereby improving the safety performance, cycle performance and rate performance of the battery.
[0017] Preferably, the raw materials for preparing the homogeneous gel buffer layer include polymer, lithium salt and ionic liquid.
[0018] Preferably, the polymer includes any one or a combination of at least two of polyethylene glycol methyl ether acrylate (PEGMEA), polyethylene glycol diacrylate (PEGDA), polypropylene glycol methyl ether acrylate (PPGMEA) or polypropylene glycol diacrylate (PPGDA), preferably a combination of polyethylene glycol methyl ether acrylate and polyethylene glycol diacrylate.
[0019] In the present invention, the ether oxygen bonds in PEGMEA and PEGDA can be + Coordination occurs, increasing Li + The migration number in the electrolyte, the higher the Li + The transfer number means that during the charging process, more Li + It can quickly migrate from the positive electrode to the negative electrode and deposit evenly on the negative electrode surface, reducing the local accumulation and concentration polarization of lithium ions, thereby reducing the driving force for the growth of lithium dendrites. At the same time, the uniform single-phase system formed by in-situ polymerization of PEGMEA and PEGDA has high mechanical strength and elastic modulus, the transmission of lithium ions in it is relatively smooth, and the ionic conductivity is relatively high.
[0020] Preferably, the lithium salt includes any one of lithium borate, lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium difluorooxalatoborate or lithium dioxalatoborate, or a combination of at least two thereof.
[0021] Preferably, the ionic liquid comprises 1-butyl-3-methylimidazolium hexafluorophosphate (BMIMPF 6 ), any one of 1-ethyl-3-methylimidazolium tetrafluoroborate or 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt or a combination of at least two thereof.
[0022] Preferably, the mass ratio of the polymer, lithium salt and ionic liquid is (30-70):(5-20):(10-50), wherein the selection range of the polymer "30-70" can be, for example, 30, 40, 50, 60 or 70, etc., the selection range of the lithium salt "5-20" can be, for example, 5, 10, 15 or 20, etc., and the selection range of the ionic liquid "10-50" can be, for example, 10, 20, 30, 40 or 50, etc.
[0023] Preferably, the material of the porous intermediate layer includes a porous lithium fast ion conductor material and a conductive agent.
[0024] In the present invention, porous lithium fast ion conductor material refers to a type of material with a large number of pore structures inside that can quickly transport lithium ions. The size, shape and distribution of the pores vary depending on the preparation method and conditions of the material. These pores provide additional channels and spaces for the migration of lithium ions, allowing lithium ions to move more quickly in the material, thereby improving the ionic conductivity of the material.
[0025] Preferably, the porosity of the porous intermediate layer is 30-60%, for example, 30%, 40%, 50% or 60%.
[0026] In the present invention, the porous intermediate layer with appropriate porosity helps to form a continuous ion conduction path, can provide additional conduction sites, enhance the ion conduction performance, and improve the power density of the battery.
[0027] Preferably, the average pore size of the porous intermediate layer is 10-50 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm or 50 nm.
[0028] Preferably, the porous lithium fast ion conductor material includes sulfide-based porous materials, oxide-based porous materials and polymer-based porous materials.
[0029] Preferably, the oxide-based porous material comprises Li 1.5 Nb 0.4 Ti 1.5 (PO 4) 3 (LNTP), Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 or Li 0.35 La 0.55 TiO 3 Any one or a combination of at least two of the following.
[0030] Preferably, the material of the polymer base layer comprises polycarbonate and nanofiber material.
[0031] In the present invention, the nanofiber material imparts greatly enhanced mechanical strength and enhanced interfacial stability to the polymer substrate layer, because the nanofiber material not only has an extremely high modulus to enhance mechanical properties and Li dendrite blocking ability, thereby enhancing operational safety, but also effectively reduces the crystallinity of polycarbonate.
[0032] Preferably, the polycarbonate includes any one of polypropylene carbonate, polyethylene carbonate or polybutylene carbonate, or a combination of at least two thereof.
[0033] Preferably, the nanofiber material comprises polyimide and / or polyacrylonitrile.
[0034] Preferably, the material of the polymer base layer further includes a plasticizer.
[0035] In the present invention, the added plasticizer can increase the solubility of the lithium salt and inhibit the crystallization of the polycarbonate, thereby significantly improving the ionic conductivity of the overall electrolyte membrane.
[0036] Preferably, the mass ratio of the polypropylene carbonate, nanofiber polyimide and plasticizer is (40-80):(10-30):(10-30), wherein the selection range of polypropylene carbonate "40-80" can be, for example, 40, 50, 60, 70 or 80, etc., the selection range of nanofiber polyimide "10-30" can be, for example, 10, 15, 20, 25 or 30, etc., and the selection range of plasticizer "10-30" can be, for example, 10, 15, 20, 25 or 30, etc.
[0037] Preferably, the plasticizer includes any one of succinonitrile, dioctyl adipate or dibutyl phthalate, or a combination of at least two thereof.
[0038] Preferably, the thickness of the three-dimensional composite solid electrolyte membrane is 25-70 μm, for example, 25 μm, 30 μm, 40 μm, 50 μm, 60 μm or 70 μm.
[0039] Preferably, the tensile strength of the three-dimensional composite solid electrolyte membrane is 5-10 MPa, for example, 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa or 10 MPa.
[0040] Preferably, the ionic conductivity of the three-dimensional composite solid electrolyte membrane is 1.2-2.5 mS / cm, for example, it may be 1.2 mS / cm, 1.5 mS / cm, 2 mS / cm, 2.2 mS / cm or 2.5 mS / cm.
[0041] In a second aspect, the present invention provides a method for preparing the three-dimensional composite solid electrolyte membrane as described in the first aspect, the preparation method comprising the following steps:
[0042] A polymer base layer, a porous middle layer and a homogeneous gel buffer layer are sequentially deposited on a substrate to obtain the homogeneous gel buffer layer.
[0043] Preferably, the method for depositing the polymer substrate layer comprises the following steps:
[0044] The polycarbonate, the nanofiber material and the organic solvent are mixed to obtain a suspension, and then a plasticizer is added to obtain a slurry.
[0045] The slurry is coated on the substrate to obtain a polymer base layer.
[0046] Preferably, the method for depositing the porous intermediate layer comprises the following steps:
[0047] A porous lithium fast ion conductor material, a conductive agent and an organic solvent are mixed to obtain a mixed solution, and then the mixed solution is coated on the surface of the polymer base layer to obtain a porous intermediate layer.
[0048] Preferably, the deposition method of the homogeneous gel buffer layer comprises the following steps:
[0049] The polymer and the ionic liquid are mixed to obtain a mixed solution, and then a lithium salt and an initiator are added to carry out an in-situ polymerization reaction to obtain a polymer solution.
[0050] The polymer solution is coated on the surface of the porous intermediate layer to obtain a homogeneous gel buffer layer.
[0051] Preferably, the initiator includes any one of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide or cumene hydroperoxide, or a combination of at least two thereof.
[0052] Preferably, the temperature of the in-situ polymerization reaction is 45-70°C, for example, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, etc.
[0053] Preferably, the preparation method comprises the following steps:
[0054] (1) At 30-60° C. (for example, 30° C., 40° C., 50° C. or 60° C.), polypropylene carbonate is stirred and dissolved in an organic solvent, and then nanofiber polyimide is added and stirred and mixed to obtain a suspension.
[0055] Under stirring conditions, a plasticizer is added to the suspension to form a slurry, and then the slurry is sprayed on the surface of a substrate to form a polymer base layer.
[0056] (2) SiO x The etched porous lithium fast ion conductor material and the conductive agent are dissolved in an organic solvent to obtain a mixed solution, and then the mixed solution is scraped and coated on the surface of the polymer base layer, and a porous intermediate layer is formed after drying.
[0057] Among them, SiO x The mass ratio of the etched porous lithium fast ion conductor material to the conductive agent is 1:(0.1-0.5) (for example, it can be 1:0.1, 1:0.2, 1:0.3, 1:0.4 or 1:0.5, etc.).
[0058] (3) stirring and dissolving the polymer in the ionic liquid, and then adding a lithium salt and stirring and mixing to obtain a mixed solution; adding an initiator to the mixed solution, and performing an in-situ polymerization reaction at 45-70° C. to obtain a polymer solution; pouring the polymer solution on the surface of the porous intermediate layer to form a homogeneous gel buffer layer, thereby obtaining the three-dimensional composite solid electrolyte membrane.
[0059] It should be noted that SiO x The x in the equation is between 0 and 2, for example, 0.5, 1, 1.5 or 2.
[0060] The present invention is to SiO x The preparation method of the etched porous lithium fast ion conductor material is not limited, and is exemplified as follows: when Si and SiO 2 After premixing, it is placed in a plasma generator, and the high-energy particles (such as ions and electrons) in the plasma react with Si and SiO 2 The mixture, that is, SiOx (where x is between 0-2), interacts with each other. During the plasma etching process, high-energy particles hit the surface of the material to be etched, breaking the Si-Si, Si-O and OO bonds. 2 Due to the chemical and structural differences, their etching rates are different in a plasma environment, which leads to the formation of a porous structure on the surface of the material to be etched. For example, Si atoms may be larger than SiO 2 The Si atoms in the plasma are more easily attacked by active species in the plasma, and thus are preferentially etched away, leaving pores.
[0061] In a third aspect, the present invention provides an all-solid-state lithium metal battery, comprising a positive electrode sheet, a negative electrode sheet, and the three-dimensional composite solid electrolyte membrane described in the first aspect located between the positive electrode sheet and the negative electrode sheet.
[0062] In the three-dimensional composite solid electrolyte membrane, the homogeneous gel buffer layer is close to the negative electrode sheet, and the polymer base layer is close to the positive electrode sheet.
[0063] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0064] Compared with the prior art, the present invention has the following beneficial effects:
[0065] In the three-dimensional composite solid electrolyte membrane designed by the present invention, the homogeneous gel buffer layer has high mechanical strength and elastic modulus, wherein the lithium ion transmission is smooth, the ion conductivity is high, and it is in direct contact with the lithium metal negative electrode. When lithium dendrites are generated, the buffer structure of the homogeneous gel buffer layer can apply a certain resistance to limit the growth and extension of lithium dendrites, and prevent them from piercing the diaphragm to cause a battery short circuit; the porous intermediate layer can increase the contact area between the membrane layer on both sides and the electrode, provide more transmission channels for lithium ions, reduce the resistance of ion transmission, thereby improving the ion conductivity, enabling the battery to charge and discharge more quickly, and improving the rate performance of the battery. At the same time, the porous intermediate layer also has excellent mechanical stability, which enables the three-dimensional composite solid electrolyte membrane to better withstand the stress generated by the volume change of the electrode material during the battery charging and discharging process, reduce the risk of membrane rupture and damage, and improve the cycle life of the battery; the polymer substrate layer has excellent mechanical strength and interface stability. Therefore, the three membrane layers cooperate with each other to effectively inhibit the chemical side reactions between the three-dimensional composite solid electrolyte membrane and the positive and negative electrodes, reduce the interface impedance, and improve the overall electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] Figure 1 This is a schematic diagram of the structure of the three-dimensional composite solid electrolyte membrane provided in Example 1 of the present invention.
[0067] Among them, 1-polymer base layer; 2-porous middle layer; 3-homogeneous gel buffer layer. DETAILED DESCRIPTION
[0068] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0069] Example 1
[0070] This embodiment provides a three-dimensional composite solid electrolyte membrane, and its structural schematic diagram is as follows: Figure 1 As shown, it includes a homogeneous gel buffer layer 3, a porous middle layer 2 and a polymer base layer 1 which are stacked.
[0071] The thickness of the homogeneous gel buffer layer 3 is 12 μm, the thickness of the porous intermediate layer 2 is 20 μm, the thickness of the polymer base layer 1 is 15 μm, the thickness of the three-dimensional composite solid electrolyte membrane is 47 μm, and the thickness ratio of the homogeneous gel buffer layer 3, the porous intermediate layer 2 and the polymer base layer 1 is 0.8:1.33:1.
[0072] The raw materials for preparing the homogeneous gel buffer layer 3 include polymer, lithium salt and ionic liquid, the polymer includes PEGMEA and PEGDA, the lithium salt is lithium borate, and the ionic liquid is BMIMPF. 6 The mass ratio of the polymer, lithium salt and ionic liquid is 50:10:40; the material of the porous intermediate layer 2 includes a porous lithium fast ion conductor material and a conductive agent, the porous lithium fast ion conductor material is LNTP, the conductive agent is conductive carbon black, the porosity of the porous intermediate layer 2 is 40%, and the average pore size is 20nm; the material of the polymer base layer 1 includes polypropylene carbonate, polyimide and succinonitrile, and the mass ratio of polypropylene carbonate, polyimide and succinonitrile is 60:20:20.
[0073] This embodiment also provides a method for preparing the above three-dimensional composite solid electrolyte membrane, the preparation method comprising the following steps:
[0074] (1) Under the condition of 40° C., polypropylene carbonate is stirred and dissolved in N,N-dimethylformamide by using a magnetic stirrer to form a uniform and transparent solution, and then nanofiber polyimide is added and stirred and mixed, and ultrasonic dispersion is performed at the same time to obtain a stable suspension.
[0075] Under stirring conditions, a plasticizer is added dropwise into the suspension to form a uniform slurry, and then the slurry is sprayed onto the surface of a polyethylene terephthalate substrate by a spray gun to form a polymer base layer.
[0076] (2) SiO x The etched porous LNTP and conductive carbon black are dissolved in N-methylpyrrolidone to obtain a mixed solution, and then the mixed solution is evenly scraped and coated on the surface of the polymer base layer, and a porous intermediate layer is formed after drying.
[0077] Among them, SiO x The mass ratio of the etched porous LNTP and the conductive carbon black was 1:0.1.
[0078] (3) Place PEGMEA and PEGDA into ionic liquid BMIMPF 6 in a reaction vessel and fully dissolve it under stirring; after the polymer is completely dissolved, lithium borate is slowly added to the reaction vessel and continued to be stirred until the lithium borate is completely dissolved to form a uniform and transparent solution; azobisisobutyronitrile is added and the temperature is raised to 55° C. for in-situ polymerization reaction; when the polymer solution becomes viscous, cannot flow and has a certain elasticity, it is poured on the surface of the porous intermediate layer to form a homogeneous gel buffer layer to obtain the three-dimensional composite solid electrolyte membrane.
[0079] Example 2
[0080] This embodiment provides a three-dimensional composite solid electrolyte membrane, including a homogeneous gel buffer layer, a porous middle layer and a polymer base layer which are stacked.
[0081] The thickness of the homogeneous gel buffer layer is 5 μm, the thickness of the porous intermediate layer is 10 μm, the thickness of the polymer base layer is 10 μm, the thickness of the three-dimensional composite solid electrolyte membrane is 25 μm, and the thickness ratio of the homogeneous gel buffer layer, the porous intermediate layer and the polymer base layer is 0.5:1:1.
[0082] The raw materials for preparing the homogeneous gel buffer layer include polymer, lithium salt and ionic liquid, the polymer includes PEGMEA and PEGDA, the lithium salt is lithium hexafluorophosphate, and the ionic liquid is BMIMPF 6 The mass ratio of the polymer, lithium salt and ionic liquid is 60:15:25; the material of the porous intermediate layer includes a porous lithium fast ion conductor material and a conductive agent, the porous lithium fast ion conductor material is LNTP, the conductive agent is conductive carbon black, the porosity of the porous intermediate layer is 30%, and the average pore size is 20nm; the material of the polymer base layer includes polypropylene carbonate, polyimide and succinonitrile, and the mass ratio of polypropylene carbonate, polyimide and succinonitrile is 55:15:30.
[0083] This embodiment also provides a method for preparing the above three-dimensional composite solid electrolyte membrane, the preparation method comprising the following steps:
[0084] (1) Under the condition of 50° C., polypropylene carbonate is stirred and dissolved in N,N-dimethylformamide by using a magnetic stirrer to form a uniform and transparent solution, and then nanofiber polyimide is added and stirred and mixed, and ultrasonic dispersion is performed at the same time to obtain a stable suspension.
[0085] Under stirring conditions, a plasticizer is added dropwise into the suspension to form a uniform slurry, and then the slurry is sprayed onto the surface of a polyethylene terephthalate substrate by a spray gun to form a polymer base layer.
[0086] (2) SiO x The etched porous LNTP and conductive carbon black are dissolved in N-methylpyrrolidone to obtain a mixed solution, and then the mixed solution is evenly scraped and coated on the surface of the polymer base layer, and a porous intermediate layer is formed after drying.
[0087] Among them, SiO x The mass ratio of the etched porous LNTP and the conductive carbon black was 1:0.1.
[0088] (3) Place PEGMEA and PEGDA into ionic liquid BMIMPF 6 in a reaction vessel and fully dissolve it under stirring; after the polymer is completely dissolved, slowly add lithium hexafluorophosphate into the reaction vessel and continue stirring until the lithium borate is completely dissolved to form a uniform and transparent solution; add azobisisobutyronitrile and heat to 45°C for in-situ polymerization; when the polymer solution becomes viscous, cannot flow and has a certain elasticity, pour it on the surface of the porous intermediate layer to form a homogeneous gel buffer layer, thereby obtaining the three-dimensional composite solid electrolyte membrane.
[0089] Example 3
[0090] This embodiment provides a three-dimensional composite solid electrolyte membrane, including a homogeneous gel buffer layer, a porous middle layer and a polymer base layer which are stacked.
[0091] The thickness of the homogeneous gel buffer layer is 20 μm, the thickness of the porous intermediate layer is 30 μm, the thickness of the polymer base layer is 20 μm, the thickness of the three-dimensional composite solid electrolyte membrane is 70 μm, and the thickness ratio of the homogeneous gel buffer layer, the porous intermediate layer and the polymer base layer is 1:0.67:1.
[0092] The raw materials for preparing the homogeneous gel buffer layer include polymer, lithium salt and ionic liquid, the polymer includes PEGMEA and PEGDA, the lithium salt is lithium borate, and the ionic liquid is BMIMPF 6The mass ratio of the polymer, lithium salt and ionic liquid is 40:20:40; the material of the porous intermediate layer includes a porous lithium fast ion conductor material and a conductive agent, the porous lithium fast ion conductor material is LNTP, the conductive agent is conductive carbon black, the porosity of the porous intermediate layer is 35%, and the average pore size is 30nm; the material of the polymer base layer includes polypropylene carbonate, polyimide and succinonitrile, and the mass ratio of polypropylene carbonate, polyimide and succinonitrile is 50:30:20.
[0093] This embodiment also provides a method for preparing the above three-dimensional composite solid electrolyte membrane, the preparation method comprising the following steps:
[0094] (1) Under the condition of 45° C., polypropylene carbonate is stirred and dissolved in N,N-dimethylformamide by using a magnetic stirrer to form a uniform and transparent solution, and then nanofiber polyimide is added and stirred and mixed, and ultrasonic dispersion is performed at the same time to obtain a stable suspension.
[0095] Under stirring conditions, a plasticizer is added dropwise into the suspension to form a uniform slurry, and then the slurry is sprayed onto the surface of a polyethylene terephthalate substrate by a spray gun to form a polymer base layer.
[0096] (2) SiO x The etched porous LNTP and conductive carbon black are dissolved in N-methylpyrrolidone to obtain a mixed solution, and then the mixed solution is evenly scraped and coated on the surface of the polymer base layer, and a porous intermediate layer is formed after drying.
[0097] Among them, SiO x The mass ratio of the etched porous LNTP and the conductive carbon black was 1:0.3.
[0098] (3) Place PEGMEA and PEGDA into ionic liquid BMIMPF 6 in a reaction vessel and fully dissolve it under stirring; after the polymer is completely dissolved, lithium borate is slowly added to the reaction vessel and continued to be stirred until the lithium borate is completely dissolved to form a uniform and transparent solution; azobisisobutyronitrile is added and the temperature is raised to 70°C for in-situ polymerization reaction; when the polymer solution becomes viscous, cannot flow and has a certain elasticity, it is poured on the surface of the porous intermediate layer to form a homogeneous gel buffer layer to obtain the three-dimensional composite solid electrolyte membrane.
[0099] Example 4
[0100] The difference between this embodiment and embodiment 1 is that the thickness of the homogeneous gel buffer layer is adjusted to 5 μm, so that the thickness ratio of the homogeneous gel buffer layer to the polymer base layer is 0.33:1.
[0101] The rest of the preparation methods and parameters were the same as those in Example 1.
[0102] Example 5
[0103] The difference between this embodiment and embodiment 1 is that the thickness of the homogeneous gel buffer layer is adjusted to 20 μm, so that the thickness ratio of the homogeneous gel buffer layer to the polymer base layer is 1.33:1.
[0104] The rest of the preparation methods and parameters were the same as those in Example 1.
[0105] Example 6
[0106] The difference between this embodiment and embodiment 1 is that the thickness of the porous intermediate layer is adjusted to 5 μm, so that the thickness ratio of the porous intermediate layer to the polymer base layer is 0.33:1.
[0107] The rest of the preparation methods and parameters were the same as those in Example 1.
[0108] Example 7
[0109] The difference between this embodiment and embodiment 1 is that the thickness of the porous intermediate layer is adjusted to 30 μm, so that the thickness ratio of the porous intermediate layer to the polymer base layer is 2:1.
[0110] The rest of the preparation methods and parameters were the same as those in Example 1.
[0111] Example 8
[0112] The difference between this embodiment and embodiment 1 is that the porosity of the porous intermediate layer is 20%.
[0113] The rest of the preparation methods and parameters were the same as those in Example 1.
[0114] Example 9
[0115] The difference between this embodiment and embodiment 1 is that the porosity of the porous intermediate layer is 70%.
[0116] The rest of the preparation methods and parameters were the same as those in Example 1.
[0117] Example 10
[0118] The difference between this embodiment and embodiment 1 is that no plasticizer is added in step (1).
[0119] The rest of the preparation methods and parameters were the same as those in Example 1.
[0120] Comparative Example 1
[0121] The difference between this comparative example and Example 1 is that the SiO xThe etched porous LNTP is replaced by a non-porous LNTP, ie, the porous intermediate layer is replaced by a non-porous intermediate layer.
[0122] The rest of the preparation methods and parameters were the same as those in Example 1.
[0123] Comparative Example 2
[0124] The difference between this comparative example and Example 1 is that no porous intermediate layer is provided.
[0125] The rest of the preparation methods and parameters were the same as those in Example 1.
[0126] Performance Testing
[0127] The three-dimensional composite solid electrolyte membrane provided in the above-mentioned embodiments and comparative examples was tested for tensile strength and ionic conductivity, wherein the tensile strength test method is: the three-dimensional composite solid electrolyte membrane is cut into specified specimens, and an electronic universal testing machine is used to calculate the tensile strength using the tensile strength calculation formula (tensile strength = maximum tensile force value / original cross-sectional area) to obtain the tensile strength value of the three-dimensional composite solid electrolyte membrane; the ionic conductivity test method is the DC polarization method.
[0128] In addition, the three-dimensional composite solid electrolyte membrane provided in the above embodiments and comparative examples is used to assemble an all-solid-state lithium metal battery, and the specific steps include:
[0129] Using NCM811 as the positive electrode and lithium metal as the negative electrode, the three-dimensional composite solid electrolyte membrane is sandwiched between the positive and negative electrodes, and then the battery shell is sealed, and the positive and negative electrode sheets are welded to the electrode leads on the battery shell to obtain an all-solid-state lithium metal battery.
[0130] The above-mentioned all-solid-state lithium metal battery was tested for cycle performance and rate performance, wherein the test conditions for cycle performance were: 0.2C charging to 4.25V, 0.2C discharging to 3V, 200 cycles, capacity retention rate = capacity in the 200th week / capacity in the 1st week × 100%; the test conditions for rate performance were: 0.1C charging to 4.25V, 0.1C discharging to 3V, 5 cycles, recording the average capacity; 1.0C charging to 4.25V, 1.0C discharging to 3V, 5 cycles, recording the average capacity; rate performance = 1.0C average capacity / 0.1C average capacity × 100%.
[0131] The above test results are shown in Table 1.
[0132] Table 1
[0133]
[0134]
[0135] analyze:
[0136] The three-dimensional composite solid electrolyte membrane designed by the present invention has excellent mechanical properties and ionic conductivity, and the all-solid-state lithium metal battery prepared thereon has excellent cycle performance and rate performance.
[0137] By comparing Example 1 with Examples 4-5, it can be seen that if the thickness ratio of the homogeneous gel buffer layer and the polymer base layer is too small, it is not conducive to alleviating the stress generated by the volume change of the electrode material during the charge and discharge process, because the thinner gel buffer layer is difficult to effectively disperse the pressure applied by the volume change of the electrode, resulting in the polymer base layer being more susceptible to stress damage, which may further cause the electrolyte membrane to rupture or separate from the electrode, affecting the cycle stability of the battery; if the thickness ratio of the homogeneous gel buffer layer and the polymer base layer is too large, it is not conducive to maintaining the overall mechanical strength of the electrolyte membrane, because the homogeneous gel buffer layer is relatively too thick, and its own mechanical properties are not as good as the polymer base layer, which will make the electrolyte membrane unable to maintain a good shape and structural integrity when subjected to external mechanical forces, manifested as low tensile strength.
[0138] By comparing Example 1 with Examples 6-7, it can be seen that if the thickness ratio of the porous intermediate layer and the polymer base layer is too small, it is not conducive to improving the ion transmission efficiency of the electrolyte membrane, because the thinner porous intermediate layer provides limited ion transmission channels, which increases the resistance to ion migration in the electrolyte membrane, which will lead to low ion conductivity of the battery during the charge and discharge process; if the thickness ratio of the porous intermediate layer and the polymer base layer is too large, it is not conducive to ensuring the mechanical stability of the solid electrolyte membrane, because the porous intermediate layer is relatively too thick, its structure is relatively loose, and its mechanical strength is weak. When facing external pressure, it cannot provide sufficient support for the electrolyte membrane, which can easily cause the electrolyte membrane to deform, thereby affecting the cycle and rate performance of the battery.
[0139] By comparing Example 1 with Examples 8-9, it can be seen that if the porosity of the porous intermediate layer is too small, it is not conducive to the rapid migration of ions, because lower porosity means fewer and narrower ion transmission channels. During the battery charging and discharging process, the resistance of ions passing through the electrolyte membrane increases, which will cause the internal resistance of the battery to increase, thereby affecting the battery's rate performance and making it difficult for the battery to charge and discharge quickly at high current density; if the porosity of the porous intermediate layer is too large, it is not conducive to the mechanical integrity of the electrolyte membrane, because there are too many and large pores, which will make the structure of the porous intermediate layer loose, and when the stress is generated by the volume change of the electrode material, it is easy to collapse, thereby destroying the overall structure of the electrolyte membrane, resulting in internal short circuit of the battery or poor contact between the electrolyte and the electrode, and ultimately affecting the battery's cycle performance.
[0140] From the comparison between Example 1 and Example 10, it can be seen that if no plasticizer is added in step (1), the solubility of the lithium salt will be reduced, and it will be disadvantageous to inhibit the crystallization of polycarbonate, thereby reducing the ionic conductivity of the overall electrolyte membrane.
[0141] From the comparison between Example 1 and Comparative Example 1, it can be seen that if the porous intermediate layer is replaced by a non-porous intermediate layer, it is not conducive to the rapid transportation of lithium ions, thereby reducing the rate performance of the battery.
[0142] By comparing Example 1 with Comparative Example 2, it can be seen that if a porous intermediate layer is not provided, ions can only be transmitted in a more restricted path in the polymer base layer material, which will increase the resistance to ion transmission and slow down the ion migration speed during the charge and discharge process of the battery. Especially under high-rate charge and discharge conditions, the demand for rapid ion exchange cannot be met, thereby reducing the rate performance of the battery; when the electrode material expands or contracts, a porous intermediate layer is not provided, the solid electrolyte membrane is prone to rupture or separation from the electrode, and it is more likely to generate lithium dendrites that pierce the diaphragm and cause the battery to short-circuit.
[0143] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A three-dimensional composite solid electrolyte membrane, characterized in that: The invention comprises a homogeneous gel buffer layer, a porous middle layer and a polymer base layer which are stacked.
2. The three-dimensional composite solid electrolyte membrane according to claim 1, characterized in that: The thickness of the homogeneous gel buffer layer is 5-20 μm, preferably 5-15 μm; Preferably, the thickness of the porous intermediate layer is 10-30 μm, preferably 10-20 μm; Preferably, the thickness of the polymer substrate layer is 10-20 μm, preferably 10-15 μm; Preferably, the thickness ratio of the homogeneous gel buffer layer, the porous intermediate layer and the polymer base layer is (0.5-1):(0.6-1.5):
1.
3. The three-dimensional composite solid electrolyte membrane according to claim 1 or 2, characterized in that: The raw materials for preparing the homogeneous gel buffer layer include polymer, lithium salt and ionic liquid; Preferably, the polymer comprises any one of polyethylene glycol methyl ether acrylate, polyethylene glycol diacrylate, polypropylene glycol methyl ether acrylate or polypropylene glycol diacrylate, or a combination of at least two thereof, preferably a combination of polyethylene glycol methyl ether acrylate and polyethylene glycol diacrylate; Preferably, the lithium salt includes any one of lithium borate, lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium difluorooxalatoborate or lithium dioxalatoborate, or a combination of at least two thereof; Preferably, the ionic liquid includes any one of 1-butyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium tetrafluoroborate or 1-butyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt or a combination of at least two thereof; Preferably, the mass ratio of the polymer, the lithium salt and the ionic liquid is (30-70):(5-20):(10-50).
4. The three-dimensional composite solid electrolyte membrane according to any one of claims 1 to 3, characterized in that: The material of the porous intermediate layer includes a porous lithium fast ion conductor material and a conductive agent; Preferably, the porosity of the porous intermediate layer is 30-60%; Preferably, the average pore size of the porous intermediate layer is 10-50 nm; Preferably, the porous lithium fast ion conductor material includes sulfide-based porous materials, oxide-based porous materials and polymer-based porous materials; Preferably, the oxide-based porous material comprises Li 1.5 Nb 0.4 Ti 1.5 (PO4)3、Li 1.3 Al 0.3 Ti 1.7 (PO4)3 or Li 0.35 La 0.55 Any one or a combination of at least two of TiO3.
5. The three-dimensional composite solid electrolyte membrane according to any one of claims 1 to 4, characterized in that: The material of the polymer base layer includes polycarbonate and nanofiber material; Preferably, the polycarbonate comprises any one of polypropylene carbonate, polyethylene carbonate or polybutylene carbonate or a combination of at least two thereof; Preferably, the nanofiber material comprises polyimide and / or polyacrylonitrile; Preferably, the material of the polymer base layer further comprises a plasticizer; Preferably, the mass ratio of the polypropylene carbonate, nanofiber polyimide and plasticizer is (40-80):(10-30):(10-30); Preferably, the plasticizer includes any one of succinonitrile, dioctyl adipate or dibutyl phthalate, or a combination of at least two thereof.
6. The three-dimensional composite solid electrolyte membrane according to any one of claims 1 to 5, characterized in that: The thickness of the three-dimensional composite solid electrolyte membrane is 25-70 μm; Preferably, the tensile strength of the three-dimensional composite solid electrolyte membrane is 5-10 MPa; Preferably, the ionic conductivity of the three-dimensional composite solid electrolyte membrane is 1.2-2.5 mS / cm.
7. A method for preparing a three-dimensional composite solid electrolyte membrane according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: A polymer base layer, a porous middle layer and a homogeneous gel buffer layer are sequentially deposited on a substrate to obtain the homogeneous gel buffer layer.
8. The preparation method according to claim 7, characterized in that: The method for depositing the polymer substrate layer comprises the following steps: The polycarbonate, the nanofiber material and the organic solvent are mixed to obtain a suspension, and then a plasticizer is added to obtain a slurry; coating the slurry on the substrate to obtain a polymer base layer; Preferably, the method for depositing the porous intermediate layer comprises the following steps: Mixing a porous lithium fast ion conductor material, a conductive agent and an organic solvent to obtain a mixed solution, and then coating the mixed solution on the surface of the polymer base layer to obtain a porous intermediate layer; Preferably, the deposition method of the homogeneous gel buffer layer comprises the following steps: The polymer and the ionic liquid are mixed to obtain a mixed solution, and then a lithium salt and an initiator are added to perform an in-situ polymerization reaction to obtain a polymer solution; coating the polymer solution on the surface of the porous intermediate layer to obtain a homogeneous gel buffer layer; Preferably, the temperature of the in-situ polymerization reaction is 45-70°C.
9. The preparation method according to claim 7 or 8, characterized in that: The preparation method comprises the following steps: (1) Dissolving polypropylene carbonate in an organic solvent under stirring at 30-60° C., and then adding nanofiber polyimide and stirring and mixing to obtain a suspension; Under stirring conditions, adding a plasticizer to the suspension to form a slurry, and then spraying the slurry on the surface of a substrate to form a polymer base layer; (2) SiO x The etched porous lithium fast ion conductor material and the conductive agent are dissolved in an organic solvent to obtain a mixed solution, and then the mixed solution is scraped and coated on the surface of the polymer base layer, and a porous intermediate layer is formed after drying; Among them, SiO x The mass ratio of the etched porous lithium fast ion conductor material to the conductive agent is 1:(0.1-0.5); (3) stirring and dissolving the polymer in the ionic liquid, and then adding a lithium salt and stirring and mixing to obtain a mixed solution; adding an initiator to the mixed solution, and performing an in-situ polymerization reaction at 45-70° C. to obtain a polymer solution; pouring the polymer solution on the surface of the porous intermediate layer to form a homogeneous gel buffer layer, thereby obtaining the three-dimensional composite solid electrolyte membrane.
10. An all-solid-state lithium metal battery, characterized in that: The all-solid-state lithium metal battery comprises a positive electrode sheet, a negative electrode sheet, and a three-dimensional composite solid electrolyte membrane according to any one of claims 1 to 6 located between the positive electrode sheet and the negative electrode sheet; In the three-dimensional composite solid electrolyte membrane, the homogeneous gel buffer layer is close to the negative electrode sheet, and the polymer base layer is close to the positive electrode sheet.
Citation Information
Cited By
Composite metal lithium negative electrode, preparation method thereof and battery
CN121439691A